URINARY INCONTINENCE AFTER GYNECOLOGICAL SURGERY: RISK FACTORS, DIAGNOSIS, AND TREATMENT OPTIONS — A NARRATIVE REVIEW - Lewandowski, Jakub; Myszak, Denis; Szlegiel, Igor; Gwiaździńska, Oktawia; Strzykała, Anita (International Journal of Innovative Technologies in Social Science, 2026)
Introduction and purpose: Urinary incontinence after gynecological surgery remains a relevant clinical problem because it affects physical functioning, emotional well-being, sexual life, and social activity, even when the leakage itself is not severe. The aim of this review is to summarize the current evidence on the main types of urinary incontinence after gynecological procedures, preoperative and operative risk factors, diagnostic pathways, conservative and surgical treatment, treatment effectiveness, and the impact of therapy on patient quality of life. Brief description of the state of knowledge: Stress urinary incontinence is the most frequently reported form after gynecological procedures, but urgency and mixed urinary incontinence are also common, especially after more extensive pelvic surgery. Risk depends on the patient’s baseline pelvic floor status, age, obesity, parity, previous surgery, menopausal status, and the extent of dissection performed during the operation. Diagnostic work-up is based on history, physical examination, voiding diary, urinalysis, post-void residual assessment, and selected use of urodynamics or cystoscopy in more complex cases. Summary: Management should begin with accurate identification of the predominant symptom pattern and with measures that are proportionate to symptom severity. Supervised pelvic floor muscle training remains first-line treatment, while surgery is mainly reserved for persistent or severe stress urinary incontinence. Operative treatment may provide high rates of improvement, but treatment failure, recurrence, or bothersome new symptoms still occur in a relevant minority of patients and require reassessment and individualized follow-up.